Islamic Personality Principles in Religious Justice - Mely Khoironi Syafaat (Al-Mawaddah: Jurnal Studi Islam dan Hukum Keluarga (Ahwal Al-Syakhsiyyah), 2026)
Religious courts in Indonesia were established to serve the legal needs of Muslims, especially in family and inheritance matters. The application of the principle of Islamic personality is the main principle in determining the jurisdiction of the Religious Court, which means that it only applies to individuals who are Muslim. This article analyzes the normative basis, history of formation, and application of the principle of Islamic personality in the practice of religious justice in Indonesia. The research method used is juridical-normative through literature study and analysis of laws and regulations such as Law Number 7 of 1989 concerning Religious Courts and its amendments, the Compilation of Islamic Law, and Supreme Court jurisprudence. The results of the study show that this principle provides legal certainty and protection for the applicability of Islamic law for Muslims. Nevertheless, challenges remain in the context of legal pluralism and dual citizenship status that require further harmonization.